(untitled) (Iranian Journal of Kidney Diseases, 2014)
Introduction. It has been demonstrated that kidney length is associated with office blood pressure (BP) measurements. Several studies support that ambulatory BP measurements in comparison to conventional BP better correlate with hypertensive target organ damage, and that the lack of nocturnal dip in BP (nondipping) is related to an increase in the incidence of cardiovascular event in essential hypertensive patients. This study evaluated the specific relationship between kidney length, renal cortical thickness (RCT), and circadian BP in hypertensive patients. Materials and Methods. In a cross-sectional study, 144 patients with newly diagnosed essential hypertension underwent physical examination, office BP measurements, laboratory analysis, ambulatory BP monitoring, renal ultrasonography, and spot and 24-hour urine collection. Results. There were 103 dipper (71.5%) and 41(28.5%) nondipper patients. Among the dippers, 13 were extreme dippers and among nondippers 11 were reverse dippers. Most of the ambulatory BP measurements were not associated with kidney length or RCT. Kidney length and RCT were not different among dippers, extreme dippers, nondippers, and reverse dippers. The kidney length and RCT were not different between patients with white coat hypertension and sustained hypertension, either. Logistic regression analysis did not show any independent association between kidney length, RCT, and nondipping status. Conclusions. Kidney length and RCT may not be associated with circadian BP monitoring.